Catalytic Oxidation of C(sp3)H Bonds Induced by a Radical Cation Salt: Construction of 1, 4‐Dihydropyridines Using a Fragment‐Reassembly Strategy. Issue 6 (20th March 2014) - Jia, Xiaodong; Wang, Yaxin; Peng, Fangfang; Huo, Congde; Yu, Liangling; Liu, Jing; Wang, Xicun
Abstract A fragment‐reassembly strategy was applied to the construction of 1, 4‐dihydropyridines and phosphorus‐substituted 1, 4‐dihydropyridines under catalytic radical cation salt‐induced C(sp)3H functionalization of glycine derivatives. Mechanistic studies show that domino C(sp)3H bond oxidation and CN bond cleavage reactions are involved. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>